Analisis Akuntansi Persediaan Studi Kasus Pada Azko Living Plaza Sawojajar Malang - Eko Yudhi Rahmanto; Khojanah Hasan; Dra. Dwi Aggarani (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to examine and analyze the inventory accounting system applied at Azko Living Plaza Sawojajar Malang. As one of the most crucial assets in trading companies, inventory requires effective and efficient management and recording to ensure smooth business operations. This research adopts a qualitative approach with data collected through literature review, interviews, and direct field observations.The results indicate that the inventory accounting system at Azko Living Plaza has been implemented effectively. This is reflected in systematic procedures for receiving and inspecting goods, involving several units such as warehouse, administration, sales, delivery, and cashier. The recording process employs a perpetual method supported by a computerized application accessible via Android devices, which facilitates reporting and minimizes errors. Furthermore, the company applies the FIFO (First In, First Out) method for inventory valuation to reduce the risk of obsolescence or expiration.In conclusion, the inventory accounting information system at Azko Living Plaza Sawojajar Malang operates effectively, supported by a clear division of responsibilities, the use of information technology, and well-structured procedures that minimize potential errors and fraud in inventory management.